Effect of Digital Storytelling on Prospective Teachers’ Social Emotional Learning: An Experimental Study - Qureshi, Nuzhat Saadia; Iqbal, Muhammad Zafar (Annals of Human and Social Sciences, 2023)
In this study, the researchers explored the impact of Digital Storytelling on prospective teachers’ Social-Emotional Learning (SEL), encompassing their self-awareness, social awareness, self-management, relationship management, and responsible decision-making. We opted for a quasi-experimental research design for the present quantitative study. The study participants were 66 (male & female) prospective teachers enrolled in The National University of Modern Languages (NUML) Islamabad. Of these 66, 37 participants were in the control group and 29 in the experimental group. A questionnaire was used to collect data before (pre-test) and after applying intervention (post-test). Data analysis was conducted using SPSS (version 26), revealing that prospective teachers exhibited a moderate attitude towards SEL components. The results strongly support the research hypotheses, indicating that digital storytelling positively influences the social-emotional development of educators. This approach effectively fosters self-awareness, social awareness, self-management, and responsible decision-making in prospective teachers, aligning with integrating SEL into teacher training programs. Overall, the findings highlight the potential of digital storytelling as an effective method for enhancing SEL in prospective teachers.